Application of Electre Method in Election of Regional Head Candidates - Handayani, Tri Arista; R. Mahdalena Simanjorang (Sean Institute, 2023)
The Regional Head is a government in the region that is related to the authority they have in managing and regulating regional autonomy. Regional Heads are community protectors who head an area for the advancement of the region. The progress of an area depends on a regional leader. One of the requirements to become a regional head is that he must be registered with a party. A party is a political organization that follows a certain ideology that is formed with a general-purpose. In the NasDem party, Deli Serdang Regency, there was a problem where the process of selecting regional head candidates was still carried out manually without any system assistance. The ELECTRE method is a multi-criteria decision-making method based on the ranking concept using paired comparisons of alternatives based on each appropriate criterion. The ELECTRE method is used in conditions where alternatives that do not meet the criteria are eliminated, and suitable alternatives can be generated. Selection of candidates for the regional head is carried out using various criteria, but some criteria are very effective in selecting candidates for the regional head, namely KTP, Education, Organizational History, Work Experience, Vision & Mission. The percentage of accuracy is obtained from 10 times the electre calculation experiments and 1x error is found because the alternatives for each candidate are similar or the same as the other candidates causing the results do not to appear. Because from 10 experiments and 1 failure or 9 out of 10 from the Electre calculation experiments, a result is obtained, it can be concluded that the level of accuracy is (9/10) * 100% = 90%Application of Electre Method in Election of Regional Head Candidates.